Subdural Hematoma in an Infant with Glutaric Aciduria Type 1: A Case Report on Conservative Management - Lúcia Marques; Patrícia Lipari Pinto; Hugo Loureiro Cadilha; Patrícia Janeiro; Ana Gaspar (Acta Médica Portuguesa)
Glutaric aciduria type 1 is an inherited metabolic disorder associated with subdural hematomas, possibly due to the widening of external cerebrospinal fluid spaces. We present the case of an infant with macrocephaly since birth, diagnosed with glutaric aciduria type 1 through newborn screening, who exhibited accelerated cephalic growth during follow-up. At eight months of age, cranial magnetic resonance imaging revealed bilateral subdural hematomas with intracranial mass effect. The infant displayed no signs of intracranial hypertension, history of trauma, or signs of abuse. Although surgical treatment was considered, a multidisciplinary discussion led to the decision to manage conservatively with close monitoring. The patient remained clinically stable, and imaging showed a clear reduction in the dimensions of the hematomas. This case highlights that conservative management can be an effective approach for large subdural hematomas with mass effect in glutaric aciduria type 1, provided there is no associated symptomatology, thereby avoiding the risk of metabolic decompensation.